Safety Profile of Thread Lifts on the Face and Neck: An Evidence-Based Systematic Review. Issue 11 (9th November 2021) - Pham, Christine T.; Chu, Sherman; Foulad, Delila P.; Mesinkovska, Natasha A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: "Thread lifting" has quickly gained popularity as a minimally invasive treatment for facial rejuvenation. However, the effectiveness is questionable, and the safety and adverse effects are often not discussed. OBJECTIVE: To identify and discuss the adverse effects associated with various types of threads. MATERIALS AND METHODS: Studies describing the use of thread lifts were identified using a PubMed search. Inclusion criteria included studies in which barbed and nonbarbed threads were used for the face and neck. RESULTS: Fifty-nine articles consisting of 14, 222 patients (14, 134 barbed, 81 nonbarbed, and 7 combined cases) were included. The most common side effects overall were facial asymmetry ( n = 6, 143), edema/tumefaction ( n = 453), and ecchymosis ( n = 407). Serious adverse effects were rare and consisted of paresthesias, alopecia, and injuries to vessels/glands. Most adverse effects were transient and self-resolving, with the exception of contour irregularities, injuries to vessels/glands, infections, and inflammatory reactions. CONCLUSION: Most side effects associated with threads were self-resolving, whereas more serious cases subsided with treatment. Future studies are critical to further determine whether thread lifting provides long-lasting, safe, and satisfying results.